2021
DOI: 10.18196/st.v24i2.13015
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Interlayer Elektroplating Zinc pada Kekuatan Mekanik Friction Stir Spot Welding Aa1100-Ss400

Abstract: Sambungan FSSW dengan material yang berbeda banyak digunakan pada kendaraan. Namun, masalah muncul ketika material tersebut tidak tersambung dengan sempurna. Penggunaan interlayer Zn mampu meningkatkan kemampuan sambungan. Variasi penggunaan dwell time dan diameter shoulder digunakan untuk memperjelas peranan interlayer electroplating Zn. Pengujian tarik geser yang telah dilakukan membuktikan bahwa penggunaan interlayer electroplating Zn memiliki kemampuan sambungan yang lebih baik. Nilai maksimal pengujian ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…Penelitian FSSW dengan mengunakan interlayer terus dikembangkan dalam berbagai material sambungan, misalnya AA1100-AA1100 [7], [8], AA1100-SS400 [9], [10], Al-Cu [6], [11], [12], Al-Mg [13]- [16], AA5083-H112 [17]. Penelitian ini membahas pengaruh interlayer electroplating Cu pada kemampuan mekanik material AA6061-T6.…”
Section: Kata Kunci: Fssw Interlayer Cu Aa6061 Hook Defectunclassified
“…Penelitian FSSW dengan mengunakan interlayer terus dikembangkan dalam berbagai material sambungan, misalnya AA1100-AA1100 [7], [8], AA1100-SS400 [9], [10], Al-Cu [6], [11], [12], Al-Mg [13]- [16], AA5083-H112 [17]. Penelitian ini membahas pengaruh interlayer electroplating Cu pada kemampuan mekanik material AA6061-T6.…”
Section: Kata Kunci: Fssw Interlayer Cu Aa6061 Hook Defectunclassified
“…A joint without hook defects showed a shear-tensile load of 12 kN, higher than 6.9 kN in a joint with hook defects (Li et al, 2014). Meanwhile, a study was also conducted from the use of Zn electroplating interlayer and gave optimal results in tensile testing on friction stir spot welding results of 3.8 kN while for the connection value without electroplating interlayer of 2.5 kN, as well as hardness testing which resulted in a more excellent value of 63 HV greater than without using electroplating interlayer (Saputra, Sukarno and Zulaehah, 2021). In previous research, the results of microstructure testing showed that the friction stir spot welding method could change the dimensions of the grains in the welding area (Sehono and Ardianto, 2021).…”
Section: Introductionmentioning
confidence: 99%